2016
DOI: 10.3402/ejpt.v7.29700
|View full text |Cite
|
Sign up to set email alerts
|

PTSD in ICD-10 and proposed ICD-11 in elderly with childhood trauma: prevalence, factor structure, and symptom profiles

Abstract: BackgroundThe proposal for ICD-11 postulates major changes for posttraumatic stress disorder (PTSD) diagnosis, which needs investigation in different samples.AimsTo investigate differences of PTSD prevalence and diagnostic agreement between ICD-10 and ICD-11, factor structure of proposed ICD-11 PTSD, and diagnostic value of PTSD symptom severity classes.MethodConfirmatory factor analysis and latent profile analysis were used on data of elderly survivors of childhood trauma (>60 years, N=399).ResultsPTSD rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 40 publications
6
42
0
3
Order By: Relevance
“…The proposed three-factor structure of ICD-11 PTSD (Re, Av, Th) has been supported in a number of studies (e.g. Gluck, Knefel, Tran, & Lueger-Schuster, 2016; Hansen, Hyland, Armour, Shevlin, & Elklit, 2015; Tay et al, 2016). In addition, the second-order factorial structure of CPTSD in which the disorder is comprised of both PTSD and DSO has also been supported (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…The proposed three-factor structure of ICD-11 PTSD (Re, Av, Th) has been supported in a number of studies (e.g. Gluck, Knefel, Tran, & Lueger-Schuster, 2016; Hansen, Hyland, Armour, Shevlin, & Elklit, 2015; Tay et al, 2016). In addition, the second-order factorial structure of CPTSD in which the disorder is comprised of both PTSD and DSO has also been supported (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Glück, Knefel, and Lueger-Schuster (2017) in their paper ‘A network analysis of anger, shame, proposed ICD-11 PTSD, and different types of childhood trauma in foster care settings in a sample of adult survivors’ utilized network analysis to examine the relationships between childhood abuse, anger, shame, and the proposed ICD-11 PTSD symptoms in a sample of 220 adult survivors of institutional abuse. Many participants met criteria for comorbid mental disorders, over half of the sample met ICD-11 PTSD criteria, and 16.9% met the criteria for complex PTSD.…”
Section: In This Issuementioning
confidence: 99%
“…One reason for this is that disorder-level data are often highly heterogeneous: patients suffering from mental disorders such as PTSD or depression have many different symptom presentations (Fried & Nesse, 2015a; Glück, Knefel, Tran, & Lueger-Schuster, 2016; Olbert, Gala, & Tupler, 2014; Young, Lareau, & Pierre, 2014). Heterogeneity has also led to ongoing discussions about reliability and validity of DSM and ICD diagnoses (Insel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also demonstrated that the ICD-11 PTSD criteria identify only a subset of the individuals previously identified as having PTSD by the ICD-10 criteria (Barbano et al, 2018;Gluck et al, 2016;Haravuori, Kiviruusu, Suomalainen, & Marttunen, 2016;Tay et al, 2017), allowing comparisons between participants identified by the ICD-11, the ICD-10, and the ICD-10 only. Previous research has also demonstrated that the ICD-11 PTSD criteria identify only a subset of the individuals previously identified as having PTSD by the ICD-10 criteria (Barbano et al, 2018;Gluck et al, 2016;Haravuori, Kiviruusu, Suomalainen, & Marttunen, 2016;Tay et al, 2017), allowing comparisons between participants identified by the ICD-11, the ICD-10, and the ICD-10 only.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because previous research suggests that the ICD-11 criteria identify individuals with more severe PTSD symptoms (Barbano et al, 2018;Gluck et al, 2016;Haravuori et al, 2016), we also examined the contribution of PTSD symptom severity to comorbid disorders' prevalence and depression severity. The sample included emergency department (ED) patients assessed shortly after trauma exposure with follow-up assessments at 3-8 months after exposure.…”
Section: Introductionmentioning
confidence: 99%